Mass Media and Health Communication Messages: Implications for Rural Development in the 21st Century Nigeria - Aondowase, Saawuan; Udoudom, Uduak I.; Pam, Christiana (International Journal of Education, Management, and Technology, 2023)
This paper explores the role of mass media in health communication campaigns for rural development in the 21st century Nigeria. Mass media have been found to be critical components of Nigeria’s rural development because of their role in disseminating health communication messages with the aim of empowering and improving the health knowledge and skills as well as changing health behaviours of rural dwellers to improve their living conditions. The paper meticulously pinpoints the contributions of mass media in health communication; identified some select health communication programmes that succeeded in Nigeria courtesy of mass media amplification role as well as explored the challenges of mass media channels in rural health communication efforts. The paper is anchored on the agenda setting theory. The paper concluded that mass media are catalysts to rural development in Nigeria. The study recommended that communication should be the priority of government and development programme designers because of the pivotal role it plays in combating ignorance and misinformation in public health issues in Nigeria.